Unconventional Role of Caspase-6 in Spinal Microglia Activation and Chronic Pain - Temugin Berta; Jee Eun Lee; Chul-Kyu Park (Mediators of Inflammation)
Chronic pain affects ~20% of the worldwide population. The clinical management of chronic pain is mostly palliative and results in limited success. Current treatments mostly target the symptoms or neuronal signaling of chronic pain. It has been increasingly recognized that glial cells, such as microglia, and inflammatory signaling play a major role in the pathogenesis of chronic pain. Caspases (CASPs) are a family of protease enzymes involved in apoptosis and inflammation. They are pivotal components in a variety of neurological diseases. However, little is known about the role of CASPs in microglial modulation as to chronic pain. In particular, our recent studies have shown that CASP6 regulates chronic pain via microglial inflammatory signaling. Inhibition of microglia and CASP signaling might provide a new strategy for the prevention and treatment of chronic pain.